AN INTRODUCTION TO RADIOGRAPHY EXAMINATION METHOD IN THE INSTRUCTION ON WELDING - Kejanli, Haluk; Gur, Ali Kaya; Turkmen, Mustafa; Caligulu, Ugur (Int Council Materials Education, 2020)
The radiography examination method is used to detect defects both inside and on the surface in the weld seams in metals and alloys. We describe the radiography examination method for instructional purposes. We provide an example of radiographic testing of AISI 1010 steel + copper materials welded by friction welding in a direct-drive type friction-welding machine. The subsequent radiographic testing shows that such a pair can be welded with adequate strength via the friction welding technique. The amount of flash increases in all specimens with increasing rotational speed, friction pressure, and forging pressure. On the other hand, as friction time increased, the amount of flash decreases.
Keywords: steel plus copper; friction welding; radiographic testing